Antithrombotic therapy in the early phase of non-ST-elevation acute coronary syndromes: a systematic review and meta-analysis. Issue 1 (27th July 2019) - Galli, Mattia; Andreotti, Felicita; D'Amario, Domenico; Vergallo, Rocco; Vescovo, Giovanni Maria; Giraldi, Luca; Migliaro, Stefano; Ameri, Pietro; Porto, Italo; Crea, Filippo
Abstract: Aims: Despite the increasing use of early invasive strategies in non-ST-elevation acute coronary syndromes (NSTE-ACS), optimal initial antithrombotic therapy (ATT) based on the safety/efficacy profile of all guideline-recommended combinations remains crucial for the early management of both medically and invasively treated NSTE-ACS patients. Methods and results: Randomized controlled trials on ATT in NSTE-ACS/unstable angina reporting early (within 14 days) major adverse cardiovascular events (MACE) and major bleeding were selected. Overall, 3799 studies were screened, 117 clinical trials were assessed as potentially eligible, 20 trials were included in the study. According to treatment and type of intervention, nine different meta-analyses were performed including a total of 88 748 patients. A significant reduction of trial-defined MACE was found for aspirin vs. placebo [odds ratio (OR), 0.57; 95% confidence interval (CI), 0.34–0.96], heparin vs. placebo (OR, 0.38; 95% CI, 0.15–0.97), aspirin + heparin vs. placebo (OR, 0.32; 95% CI, 0.18–0.59), aspirin + heparin vs. aspirin (OR, 0.57; 95% CI, 0.42–0.79), aspirin + low molecular weight heparin (LMWH) vs. aspirin + unfractionated heparin (UFH; OR, 0.81; 95% CI, 0.69–0.95) and aspirin + ticagrelor/prasugrel + heparins vs. aspirin + clopidogrel + heparins (OR, 0.76; 95% CI, 0.62–0.94). A significant decrease in major bleeding was found only for fondaparinux vs. LMWH on the background of aspirin + clopidogrel (OR, 0.52; 95% CI, 0.44–0.62) despite a clear trend towards increased bleeding for heparin compared to aspirin, aspirin + heparin compared to placebo, aspirin + heparin compared to aspirin, aspirin + P2Y12 inhibitors + UFH/LMWH compared to aspirin + UFH/LMWH, and aspirin + ticagrelor/prasugrel + heparins compared to aspirin + clopidogrel + heparins. Conclusion: To our knowledge, these findings are the first to report the safety and efficacy of all the various combinations of currently recommended ATT for the early management of NSTE-ACS, providing a comprehensive evidence-base to guide decisions depending on the patients' bleeding risk and treatment strategy.